Uptake of environmental halophilic archaea by human dendritic cells - Krzysztof Krawczyk; Dorota Rybaczek; Camille Locht; Agata Pyrzanowska-Banasiak; Martyna Ciołek; Paulina Sicinska; Michalina Rachubik; Magdalena Kowalewicz-Kulbat (Scientific Reports)
Abstract Halophilic archaea are a group distinct from Bacteria and Eukarya, which belong to extremophiles living in highly saline environments. However, they can also exist in the human microbiome. Their impact on the human immune system is poorly known. In this study we examined the interaction of Halorhabdus rudnickae WSM-64T, isolated from the Barycz area of the Wieliczka Salt-Mine in Poland, and of Natrinema salaciae MDB25T from the brine of Lake Medee in Italy, with human monocyte-derived dendritic cells (Mo-DCs). We found that these halophilic archaea invade the cytoplasm and the nucleus of Mo-DCs, but, in contrast to intracellular bacterial pathogens, they do not cause cytotoxic effects on DCs, as no single- or double-stranded DNA breaks (SSB and DSB, respectively), nor chromatin aberrations were noted. Moreover, they did not induce cell cycle alterations, apoptosis or necrosis of DCs. Surprisingly, these halophiles were found to protect against genotoxic activities of Staphylococcus aureus enterotoxin B (SEB), as pre-incubation of the Mo-DCs with the halophilic archaea significantly reduced SEB-induced SSB and DSB, as well as cell cycle disturbance and apoptosis. Therefore, these halophilic archaea can be regarded as safe stimulators for the Mo-DCs to potentially be used as immunomodulators and protective agents for various disorders.